Measuring Innovation Everywhere: The Challenge of Better Policy, Learning, Evaluation and Monitoring - Gault, Fred (Cheltenham, UK:Elgar, 2020)
Discusses the measurement of innovation and the use of the resulting indicators to shape policy, exploring whether innovation can be measured everywhere, not just in the business sector, in a rapidly changing world. Reviews systems, innovation, and innovation policy. Details current innovation policies. Describes scoreboards and their use for monitoring existing innovation policy. Focuses on the implementation of innovation policy. Presents the general definition of innovation applicable in all economic sectors and considers the importance of language in the innovation discourse. Provides the conceptual framework for the specification of the statistical measurement of innovation. Addresses non-sector-specific innovation in the informal economy, green economy, social innovation, and innovation resulting from the use of general-purpose technologies. Examines global challenges for innovation such as sustainability restrictions. Considers the future of innovation in the digital economy, informal economy, and social innovation. Gault is Professorial Fellow at UNU-MERIT, Professor Extraordinary at Tshwane University of Technology, and Visiting Professor at the University of Johannesburg. Index.
Pages: xvii, 128
Keywords: Mesure d'impact; Réservé UdeM